Study of impurity transport in HL-2A ECRH L-mode plasmas with radially different ECRH power depositions. (15th March 2018) - Cui, Z.Y.; Zhang, K.; Morita, S.; Ji, X.Q.; Ding, X.T.; Xu, Y.; Sun, P.; Gao, J.M.; Dong, C.F.; Zheng, D.L.; Li, Y.G.; Jiang, M.; et al.
Abstract: In HL-2A, an inverse sawtooth oscillation is observed with a long-lasting m / n   =  1/1 mode during ECRH phase with power deposition inside sawtooth inversion radius (inner-deposited ECRH), while a normal sawtooth instead appears when the ECRH power is deposited outside sawtooth inversion radius (outer-deposited ECRH). Aluminum is then injected as a trace impurity with laser blow-off (LBO) method into the inner- and outer-deposited ECRH phases of HL-2A discharges to investigate the effect of ECRH on impurity transport. Temporal behavior of soft x-ray (SXR) array signals is analyzed with a 1D impurity transport code, and radial structures of impurity transport coefficients are obtained. The result shows that the radial transport of Al ions is strongly enhanced during the inner-deposited ECRH phase. In particular, an outward convection velocity is developed with positive values of 0  ⩽   V ( ρ )  ⩽  3.8 m s −1 in ρ   ⩽  0.5, while the convection velocity is inward in ρ   ⩾  0.6. In the outer-deposited ECRH discharge, on the other hand, the convection velocity takes a big negative value in ρ   ⩽  0.4 and close to zero at ρ ~ 0.6. In ohmic discharges, an inward V ( ρ ) always appears in the whole plasma radii and gradually increases toward the plasma edge (−3.2 m s −1 at ρ   =  1). The simulation result also indicates that centrally-peaked Al ion density profiles presented in the outer-deposited ECRH discharge can be flattened by the inner-deposited ECRH. Modification of impurity transport is discussed in the presence of long-lasting m / n   =  1/1 MHD mode.